2011
DOI: 10.1007/s00134-011-2382-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation through a helmet in postextubation hypoxemic patients: physiologic comparison between neurally adjusted ventilatory assist and pressure support ventilation

Abstract: Compared with PSV, NAVA improves patient-ventilator interaction and synchrony, with no difference in gas exchange, respiratory rate, and neural drive and timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 29 publications
(46 reference statements)
9
56
0
2
Order By: Relevance
“…Additionally, there were no ineffective efforts, no delayed cycling and no premature cycling during NAVA. These results are consistent with improved synchrony demonstrated in animals [21] and in low-birth-weight infants (using a single nasal prong interface) [22] with NAVA-NIV in comparison to PS-NIV as well as with improved synchrony recently demonstrated with helmet NAVA-NIV in comparison to helmet PS-NIV [23].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, there were no ineffective efforts, no delayed cycling and no premature cycling during NAVA. These results are consistent with improved synchrony demonstrated in animals [21] and in low-birth-weight infants (using a single nasal prong interface) [22] with NAVA-NIV in comparison to PS-NIV as well as with improved synchrony recently demonstrated with helmet NAVA-NIV in comparison to helmet PS-NIV [23].…”
Section: Discussionsupporting
confidence: 88%
“…New ventilation modes have also been investigated, such as neurally adjusted ventilatory assist, in order to improve patient-ventilator interaction during NIV, as recently demonstrated by Cammarota and colleagues. 13 The success of NIV depends also on the kind of helmet. In recent years, many technological efforts have been made to improve helmet features in terms of design, material, and application systems, since it has been demonstrated 13 that the helmet's specific physical characteristics may significantly affect patient-ventilator interaction, suggesting that different helmets determine different ventilator performance, even if specific ventilator settings are applied.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absence of wasted effort with the double tube circuit demonstrates the positive influence of the optimal circuit on patient-ventilator interaction and ventilator performance, as wasted effort generates patient discomfort, gas exchange deterioration, work of breathing increase, and rise in risk of NIV failure. [12][13][14][15][16][17] It is noteworthy that better interaction and performance determined significantly higher V T and neural V T values with the double tube circuit, compared to the standard circuit, at both breathing frequencies and ventilator settings, except at 30 breaths/min with the default setting; however, this condition was altered by the presence of wasted effort, which make the analysis unreliable. On the basis of our results, we suggest the use of a double tube circuit to connect the helmet to the ventilator during helmet NIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAVA has been reported to improve synchrony during NIV when a helmet is used. 146,147 Using an oronasal mask, Schmidt et al 148 reported that NAVA improved synchrony more than the use of NIV mode on a critical care ventilator. The combination of NAVA with the NIV mode seemed to offer the best compromise between good synchrony and a low level of leaks.…”
Section: Technical Aspects Which Interface?mentioning
confidence: 99%